2021
DOI: 10.1016/j.ajic.2020.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The role of facial contact in infection control: Renewed import in the age of coronavirus

Abstract: Highlights Men show higher rates of facial contact than women Rates of facial contact can vary in different social situations Fatigue and distraction increase rates of facial contact and subsequent infection risk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
1
3
1
Order By: Relevance
“…The frequency and duration of membrane HFC at each site (eyes, nose and mouth) found in the present study were different from the findings of previous studies (Kwok et al, 2015; Oh et al, 2017; Christensen et al, 2020). Hand‐to‐mouth contact has been shown to have the highest frequency in previous studies involving adults (Ng et al, 2016; Oh et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The frequency and duration of membrane HFC at each site (eyes, nose and mouth) found in the present study were different from the findings of previous studies (Kwok et al, 2015; Oh et al, 2017; Christensen et al, 2020). Hand‐to‐mouth contact has been shown to have the highest frequency in previous studies involving adults (Ng et al, 2016; Oh et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…To the authors’ knowledge, few studies have examined HFC among older patients (over 65 years); therefore, the results of the present study were compared to results of studies of other adults. The HFC frequency (43.3/2 hrs) of older people in this study was similar to that found in a study of medical students (23 times/hr; Kwok et al, 2015) and in a study of adults (22/hr; Christensen et al, 2020), while it was higher than that found by another study of students (15.7/hr; Nicas & Best, 2008), by a study of research workers (0.2–16.0 /hr; Johnston et al, 2014) and by a study of adults (14.6/hr; Wilson et al, 2021). The HFC frequency found in the present study was considered sufficient to predict respiratory disease (>15.7/hr; Nicas & Best, 2008), that is the HFC frequency of the older people in this study was high enough to transmit respiratory diseases.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations